Application of the Analysis Model for Estimating the Nutrient Content of Feed Ingredient: A Case Study of Rice Bran - Muhammad Ridla; Almira Firna Fitrianti Ludfi; Alya Nur Zahra; Mutiara Rizky Raisa; Nahrowi Nahrowi; Anuraga Jayanegara; Erica B. Laconi (Jurnal Peternakan, 2023)
In rural areas, farmers face a significant challenge due to the lack of access to chemical analysis for feed ingredients. Therefore, there is a need for a new approximate analysis model that is lightweight and easy to apply. This study aimed to address this issue by utilizing bulk and tapped density analysis to estimate the composition of rice bran samples collected from 30 rural rice mill factories across 3 districts in Indonesia. The study used a correlation formula between bulk density values and tapped density values to estimate the crude protein and crude fiber contents of the samples. The study's results revealed significant variations (p<0.05) in the quality of rice bran due to various factors. Crude protein content significantly differed (p<0.05) across districts, with Bogor and Bandung having the highest values and Cirebon the lowest. Tapped density measurements generally yielded higher crude protein content values. Similarly, there were variations (p<0.05) in crude fiber content across districts and locations, with Cirebon having the highest values and Bogor the lowest. Tapped density measurements generally resulted in higher crude fiber content values, but there were significant variations observed in different districts and locations. The rice bran from the Bogor region showed indications of being of higher quality, with higher crude protein and lower crude fiber content compared to the other two regions.